Analysis of Mathematical Connection and Students' Self Confidence in Flat-Side Space Material - Jalaludin, Muhamad Agus; Yunita, Winda; Indahsari, Ita Nur; Purwasih, Ratni (Journal of Education Reseach and Evaluation, 2018)
This research is a study to analyze the ability of mathematical connections and self-confidence in the flat-side space material for junior high school students. This research used a qualitative descriptive method. The study was conducted at 47 Bandug Junior High School in 9th grade students of SMPN 47 Bandung who had studied in a flat side room. The research subjects were ninth grade F. The data were collected in the form of a description of the test instrument and self-confidence questionnaire. The results of the study concluded: 1) the level of students' mathematical connection skills in the settlement pointed at good categories; 2) students have mastered the materials so that they could understand problems and concepts well; 3) students already have had good self-confidence.